Prognostic significance of K-ras mutations in pancreatic cancer: a meta-analysis - Tao, Lian-yuan (World J Surg Oncol, 2016)
BACKGROUND: K-ras gene mutations are common in patients with pancreatic cancer (PC); however, their prognostic value for PC remains inconclusive. This meta-analysis was performed to quantitatively evaluate the association between K-ras mutations and survival in patients with pancreatic cancer. METHODS: We performed a comprehensive search of electronic sources including MEDLINE (via PubMed), Web of Science, and the Cochrane Library. The search covered a publication period from inception to November 2015. RESULTS: Seventeen studies with a total of 2249 patients with pancreatic cancer were included in the tissue detection of this study. The meta-analysis indicated a significant association between mutant K-ras genes and overall survival (OS) (HR = 1.51, 95 % CI 1.32–1.72, P < 0.001). Moreover, further subgroup analyses by ethnicity, publication year, therapy method, cancer resectability, and gene detection method all revealed that pancreatic cancer patients with the K-ras mutation had significantly poorer OS (P < 0.05). And results from four studies with 225 patients focused on plasma K-ras mutations enhanced such association (HR = 2.23, 95 % CI 1.69–2.95, P < 0.001). CONCLUSIONS: As a prediction of poor prognosis, the detection of K-ras mutations may be a useful prognostic factor for pancreatic cancer patients.